2014
DOI: 10.1158/1535-7163.mct-13-0671
|View full text |Cite
|
Sign up to set email alerts
|

Synuclein γ Compromises Spindle Assembly Checkpoint and Renders Resistance to Antimicrotubule Drugs

Abstract: Defects in the spindle assembly checkpoint (SAC) have been proposed to contribute to the chromosomal instability in human cancers. One of the major mechanisms underlying antimicrotubule drug (AMD) resistance involves acquired inactivation of SAC. Synuclein g (SNCG), previously identified as a breast cancer-specific gene, is highly expressed in malignant cancer cells but not in normal epithelium. Here, we show that SNCG is sufficient to induce resistance to AMD-caused apoptosis in breast cancer cells and cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…SNCG is a small soluble protein that interferes with the normal mitotic checkpoint and forms a positive feedback loop with insulin-like growth factor signaling (58). SNCG promotes tumor invasion, metastasis, and resistance to antineoplastic-induced apoptosis (58)(59)(60). SNCG expression is upregulated in several common human cancers (e.g., lung, breast, prostate, colon) and is correlated with metastasis risk (61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%
“…SNCG is a small soluble protein that interferes with the normal mitotic checkpoint and forms a positive feedback loop with insulin-like growth factor signaling (58). SNCG promotes tumor invasion, metastasis, and resistance to antineoplastic-induced apoptosis (58)(59)(60). SNCG expression is upregulated in several common human cancers (e.g., lung, breast, prostate, colon) and is correlated with metastasis risk (61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%
“…Such findings stimulated the search for and development of inhibitors that target the catalytic site of the SAC kinases Aurora B and Mps1, some of which have entered clinical trials. Examples are: the Aurora kinase inhibitor AT9283, which is prescribed for the treatment of non-Hodgkin's lymphoma (Phase I completed; NCT00443976); the inhibitor PF-03814735, which is used for the treatment of histologically or cytologically confirmed malignancies (Phase I completed; NCT00424632); and the Mps1 inhibitor BAY1161909 (in Phase I trial for the treatment of solid tumours; NCT02138812) [66,67]. Unfortunately, the use of smallsized inhibitors that act as ATP-binding competitors, including those that target SAC kinases, has been of limited success.…”
Section: The Potential Of Cdc20 As a Drug Targetmentioning
confidence: 99%
“…It was demonstrated that SNCG binds to a spindle checkpoint kinase, BUB1B, thereby inducing a structural change in BUB1B. This inhibited its kinase activity and attenuated its interaction with other key checkpoint proteins, such as cell‐division cycle protein 20 (Cdc20), compromising the spindle assembly checkpoint . The lack of checkpoint function would allow cells to override G2/M arrest with aneuploidy proliferation to perpetuate genomic instability.…”
Section: Resultsmentioning
confidence: 99%
“…This inhibited its kinase activity and attenuated its interaction with other key checkpoint proteins, such as cell-division cycle protein 20 (Cdc20), compromising the spindle assembly checkpoint. 16,24,25 The lack of checkpoint function would allow cells to override G2/M arrest with aneuploidy proliferation to perpetuate genomic instability. By targeting SNCG with a specific peptide, sensitivity to paclitaxel was enhanced.…”
Section: Discussionmentioning
confidence: 99%